Analisis Faktor Yang Mempengaruhi Kepuasan Pelanggan Pada Produk Air Conditioner di Jasa Distributor - Syaifuddin, Achmad; Triana, Novera Elisa (Universitas Mercu Buana, 2023)
Customer satisfaction is crucial in determining the success or failure of a business. One of the companies engaged in air conditioning distributor services received many complaints from customers which had an impact on sales results which had decreased from previous years. The purpose of this study was to find the relationship between the variables that influence customer satisfaction, and then carry out an analysis of improvements so that the level of customer satisfaction becomes more optimal. The variables used consist of customer satisfaction (Y) as the dependent variable and independent variables, namely service quality (X1), product quality (X2) and price (X3) with each variable being measured by an indicator. Primary data was obtained from the results of questionnaires to 72 respondents using the probability sampling technique. The data obtained was then processed using the Structural Equation Modeling- Partial Least Square (SEM-PLS) method. This result Service Quality has a positive and significant effect on Customer Satisfaction. Product Quality has a positive and significant effect on Customer Satisfaction. Product prices have a positive and significant effect on customer satisfaction.